Enzymatic scarification of Anacamptis morio (Orchidaceae) seed facilitates lignin degradation, water uptake and germination. (11th February 2018) - Pierce, S.; Spada, A.; Caporali, E.; Ceriani, R. M.; Buffa, G.
Abstract: The seed coat of many species contains hydrophobic lignins, and in soil the action of microbial ligninases may contribute to release from dormancy. Laboratory use of ligninases to stimulate germination is promising because of the specific action on the seed coat, whereas chemical scarification agents may also corrode the embryo. We hypothesised that exposure of Anacamptis morio (Orchidaceae) seeds to fungal laccase would stimulate germination, and that the mechanism involves lignin degradation and increased imbibition. Germination capacity in vitro was quantified with 1 U filter‐sterilised laccase added to agar medium following autoclaving, compared to a 10% bleach solution (standard bleach surface sterilisation/scarification method used in orchid seed sowing). Lignin degradation was quantified using an optical method (phloroglucinol‐HCl staining) combined with image analysis, following experimental pre‐treatments involving immersion in laccase solution, distilled water (negative control) or bleach (positive control). Water uptake after experimental treatments was quantified as the proportion of seeds exhibiting visible uptake of an aqueous fluorochrome under UV excitation. Laccase stimulated a doubling of germination in vitro with respect to bleach surface sterilisation/scarification alone, from 23.7 to 49.8% ( P  =   0.007). Laccase and bleach methods both significantly decreased the optical signal of phloroglucinol (for laccase, to 79.9 ± 1.3% of controls;anova : F = 10.333, P  =   0.002). Laccase resulted in a modest but highly significant ( P  <   0.0001) increase in water uptake with respect to the control (11.7%; cf 99.4% for bleach). Laccase scarification can stimulate germination of A. morio through a mechanism of targeted seed coat degradation. The results demonstrate the potential of this relatively non‐invasive enzymatic scarification technique.